Analysis of Opportunities and Threats of Social Media in The Formation of Student Character Viewed from The Perspective of Islamic Education - Wiratama, Hanif Syairafi; Hafidz, H (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Social media could be a social structure that comes from people and organizations bound by the closeness of their clients. Social media is online media (online media) that's utilized as a implies of online social affiliation on the web. In social media, clients can associated with each other, communicate, share organizing and different other exercises online. Social media is made to qualify people since people as social animals, were made to socialize. Since the times are getting more progressed, whose primary reason is to facilitate clients or social media clients to be able to associate with somebody in one nation, indeed between nations and between landmasses for all intents and purposes and not squander time or give comfort for clients to socialize. But in today's cutting edge period, social media not as it were capacities as regular, it turns out that social media has impacts on pese character instruction.